2011
DOI: 10.7547/1010390
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Joint Forces of the Subtalar Complex via HyProCure Sinus Tarsi Stent

Abstract: Placement of the HyProCure subtalar stabilization stent in a hyperpronated foot prevents excessive talar subluxation and assists in proper distribution of the axial loads on the subtalar facet joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The lateral conical portion of the device prevents anterior deviation of the lateral process of the talus and thus stabilizes the sinus portion of the sinus tarsi. Recently, Graham et al (20) conducted a biomechanical investigation on adult human cadaver specimens, in which the distribution of forces on the anterior and posterior aspects of the talocalcaneal joint was studied. They reported that HyProCure Ò promoted uniform distribution of the axial loads and prevented excessive talar subluxation over the calcaneus, which led to improved talotarsal biomechanics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lateral conical portion of the device prevents anterior deviation of the lateral process of the talus and thus stabilizes the sinus portion of the sinus tarsi. Recently, Graham et al (20) conducted a biomechanical investigation on adult human cadaver specimens, in which the distribution of forces on the anterior and posterior aspects of the talocalcaneal joint was studied. They reported that HyProCure Ò promoted uniform distribution of the axial loads and prevented excessive talar subluxation over the calcaneus, which led to improved talotarsal biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…It is our belief that asymptomatic patients with RTTD should also be treated, because stabilization of the TTJ complex could prevent or decrease the development of secondary conditions and therefore prevent or decrease the associated economic burden of this disorder, such as time off work and money spent on treatment. Previous reports have indicated that a minimally invasive procedure involving placement of the HyProCure Ò (GraMedica, Macomb, MI) device in the sinus/ canalis tarsi can effectively stabilize the TTJ complex (18)(19)(20). HyProCure Ò (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distal and plantar articular facets of the talus interact with the calcaneus and navicular to form the talotarsal joint (TTJ). The large posterior talocalcaneal joint is responsible to accept a vertical force as much as 80% at heel strike that reduces to slightly greater than 50% of the weightbearing forces at mid-stance (11,12). These forces occur posterior to the posterior aspect of the sinus tarsi ( Figure 1A).…”
Section: Hindfoot Alignment and Biomechanicsmentioning
confidence: 99%
“…A stable TTM leads to a specific amount of motion between these bones to properly distribute the weight-bearing forces. It acts as a torque converter transferring the forces from the leg through the foot and onto the weight-bearing surface below, and also transforming the ground reaction forces (GRF) acts on the foot into transverse plane rotations of the femoral and tibial components (2)(3)(4)(5). The stability of the talus on the tarsal mechanism depends mainly on the contour of the articular facets followed by the peri-articular ligamentous support.…”
Section: Introductionmentioning
confidence: 99%